2018
DOI: 10.1177/2396941518803807
|View full text |Cite
|
Sign up to set email alerts
|

Subskills associated with spelling ability in children with and without autism spectrum disorders

Abstract: Background and aims Effective literacy instruction demands a clear understanding of the subskills that underpin children’s reading and writing abilities. Some previous research on reading has questioned whether the same subskills support literacy acquisition for typically developing children and children with autism spectrum disorders. This study examined the subskills associated with spelling ability in a group of 20 children with ASD aged 5–12 years (ASD group). A group of 20 typically developing children ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Thus, the ability of the ASD participants in the present study to encode and maintain unfamiliar phonological sequences in memory was lower compared to their abilities in manipulating the phonological structure of words. The difference in performance between NWR and tasks of phonological awareness (phoneme reversal, elision and blending words) suggests that the ASD participants in the present study had particular difficulty in phonological memory but not in other aspects of phonological processing [63]. In other words, once the load on phonological memory is reduced, because the words presented are familiar (in the phoneme elision and blending word tasks as well as in the memory for digits task) and shorter compared to the task of phonological memory, the ability to manipulate the phonological structure of the word is significantly improved and becomes close to the age norm.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, the ability of the ASD participants in the present study to encode and maintain unfamiliar phonological sequences in memory was lower compared to their abilities in manipulating the phonological structure of words. The difference in performance between NWR and tasks of phonological awareness (phoneme reversal, elision and blending words) suggests that the ASD participants in the present study had particular difficulty in phonological memory but not in other aspects of phonological processing [63]. In other words, once the load on phonological memory is reduced, because the words presented are familiar (in the phoneme elision and blending word tasks as well as in the memory for digits task) and shorter compared to the task of phonological memory, the ability to manipulate the phonological structure of the word is significantly improved and becomes close to the age norm.…”
Section: Discussionmentioning
confidence: 52%
“…This difference may be due to limitations in phonological short-term memory in children with Down syndrome. By contrast, analyses of spelling errors by Bailey and Arciuli (2018) revealed that children with autism spectrum disorders demonstrate phonological awareness that is similar to that of their typically developing peers. Both studies contained relatively modest sample sizes.…”
Section: Spelling Analyses For the General Populationmentioning
confidence: 76%
“…As shown in the study by Treiman et al (2019a) and previous studies involving children who have developmental disabilities (e.g. Bailey and Arciuli, 2018; Lim et al, 2014), measures based on phonological awareness may be useful when working with children with lower literacy skills who produce few or no conventionally accurate spelling attempts.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, literacy seemed to be supported by many of the same underlying subskills in children with ASD as in non-ASD children. As pointed out by Bailey and Arciuli [14], potentially important issues are at stake in this context, because if there are similar concurrent predictors of literacy and literacy problems in children with ASD, then there are greater reasons to assume that standard models of (remedial) literacy instruction might be helpful also for children with ASD. From clinical and educational perspectives, this also highlights the importance of assessing literacy skills in students with ASD so that pedagogic interventions can be provided for those in need of itinstead of assuming that any literacy problems are secondary or "just part of the autism."…”
Section: Discussionmentioning
confidence: 99%
“…Guided by findings in general research on literacy [3][4][5]7] and employing a regression analytical approach, we wanted to determine if we could predict literacy subskills from the following language/ cognitive predictor skills: listening comprehension, rapid automatized naming (RAN), phonological awareness, and nonverbal cognitive ability. This has been done separately in prior studies that have focused on one or two literacy subskills [8,9,11,13,14]. The present study contributes to the current literature by including several literacy outcomes in one age-homogenous sample and using similar assessment formats.…”
Section: Introductionmentioning
confidence: 98%